Hospital Pharmacists’ Knowledge and Perceptions of Antibiotic Use and Resistance in Indonesia - Febrianti, Yosi; Lubisa, Ratu Aini; Yulianto, Yulianto; Wulandari, Denia Yuni; Wahdini, Ade indah (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
Background: Inappropriate antibiotic use in Indonesia contributes significantly to increasing antibiotic resistance, which poses a serious threat to public health. Hospital pharmacists play a crucial role in antibiotic management, so their knowledge of antibiotic use and resistance is crucial to supporting infection control efforts and the rational use of antibiotics. Objectives: To assess the knowledge and perception of hospital pharmacists on antibiotic use and resistance. Material and Methods: The research design is cross-sectional and involves collecting data through a questionnaire. Data was then analyzed using the SPSS program's Chi-square test. Results: A total of 103 responses were received, 93 (90.3%) respondents had good knowledge and 83 (80.5%) had positive perceptions of antibiotic use and resistance. Conclusions: The study's results indicate that pharmacists' knowledge of antibiotic resistance does not correlate with their perception of this issue (p=0.416).